Ceftolozane/Tazobactam: A Novel Cephalosporin/β‐Lactamase Inhibitor Combination. Issue 7 (1st July 2015) - Cho, Jonathan C.; Fiorenza, Mallory A.; Estrada, Sandy J.
<x xml:space="preserve">Abstract</x> Ceftolozane/tazobactam is a novel antipseudomonal β‐lactam/β‐lactamase inhibitor combination that is currently approved by the United States Food and Drug Administration for the treatment of complicated intraabdominal infections (cIAI) and complicated urinary tract infections (cUTI). It exhibits bactericidal properties through inhibition of bacterial cell wall biosynthesis, which is mediated through penicillin‐binding proteins (PBPs). Ceftolozane is a potent PBP3 inhibitor and has a higher affinity for PBP1b compared with other β‐lactam agents. Ceftolozane/tazobactam differs from other cephalosporins due to its increased activity against some AmpC β‐lactamases and Pseudomonas aeruginosa. The addition of tazobactam provides enhanced activity against extended‐spectrum β‐lactamase (ESBL)‐producing Enterobacteriaceae and certain anaerobic organisms. Population pharmacokinetic studies for ceftolozane and ceftolozane/tazobactam are best described by a two‐compartment model with zero‐order input and linear elimination. Similar to other cephalosporins, the best pharmacodynamic property to predict efficacy for ceftolozane/tazobactam is a concentration that remains above the minimum inhibitory concentration (MIC) for 40–50% of the dosing interval. For Enterobacteriaceae and P. aeruginosa strains, the time above the MIC (T > MIC) needed to produce bactericidal activity was much less with ceftolozane than other cephalosporins, with T > MIC requirements of approximately 30%. For currently approved indications, the dose of ceftolozane/tazobactam is 1.5 g (ceftolozane 1 g/tazobactam 0.5 g) intravenously every 8 hours given as a 1‐hour infusion. Ceftolozane has low plasma protein binding (20%) and is predominantly excreted unchanged in the urine (≥92%). Dosage adjustments are required for moderate‐to‐severe renal impairment and in patients receiving hemodialysis. Based on data from clinical trials, adverse effects due to ceftolozane/tazobactam do not differ considerably from other cephalosporins, with the most common being nausea, diarrhea, headache, and pyrexia. Ceftolozane/tazobactam is a promising new agent for the treatment of cIAI and cUTI, including those caused by multidrug‐resistant gram‐negative organisms.